Personalized Medicine Through SNP Testing for Breast Cancer Risk: Clinical Implementation. Issue 5 (18th December 2014) - Howe, Rebecca; Miron‐Shatz, Talya; Hanoch, Yaniv; Omer, Zehra B.; O'Donoghue, Cristina; Ozanne, Elissa M.
Abstract: Single nucleotide polymorphisms (SNPs) have the potential to improve personalized medicine in breast cancer care. As new SNPs are discovered, further enhancing risk classification, SNP testing may serve to complement family history and phenotypic risk factors when assessed in a clinical setting. SNP analysis is particularly relevant to high‐risk women who may seek out such information to guide their decision‐making around risk‐reduction. However, little is known about how high‐risk women may respond to SNP testing with regard to clinical decision‐making. We examined high‐risk women's interest in SNP testing for breast cancer risk through an online survey of hypothetical testing scenarios. Women stated their preferences for sharing test results and selected the most likely follow‐up action they would pursue in each of the test result scenarios (above average and below average risk for breast cancer). Four hundred seventy‐eight women participated. Most women (89 %) did not know what a SNP was prior to the study. Once SNP testing was described, 75 % were interested in SNP testing. Participants stated an interest in lifestyle interventions for risk‐reduction and wanted to discuss their testing results with their doctor or a genetic counselor. Women are interested in SNP testing and are prepared to make lifestyle changes based on testing results. Women's preference for discussing testing results with a healthcare provider aligns with the current trend towards SNP testing in a clinical setting.